Carbon nanofibers based copper/zirconia catalysts for carbon dioxide hydrogenation to methanol: Effect of copper concentration - Din, Israf Ud; Shaharun, Maizatul Shima; Naeem, A.; Tasleem, S.; Johan, Mohd Rafie (Elsevier, 2018)
A series of novel bimetallic copper/zirconia carbon nanofibers supported catalysts with different Cu contents (5–25 wt%) were synthesized via deposition precipitation method. The physicochemical characterization of the calcined catalysts was carried out by X-ray diffraction, inductively coupled plasma optical emission spectroscopy, N2 adsorption–desorption, N2O chemisorption, temperature programmed reduction, X-ray photoelectron spectroscopy, high resolution transmission electron microscopy and temperature programmed CO2 desorption. Structure-reactivity correlation for catalytic hydrogenation of CO2 to methanol was discussed in details. Reaction studies revealed 15 wt% as optimum Cu concentration for CO2 conversion to methanol with CO2/H2 feed volume ratio of 1:3. Cu surface area was found to play a vital role in methanol synthesis rate. CO2 conversion was observed to be directly proportional to the number of total basic sites. A comparative study of this novel catalyst with the recently reported data revealed the better CO2 conversion at relatively low reaction temperature.